2014
DOI: 10.1098/rspb.2014.0446
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality in a wild grazer declines under the threat of an ambush predator

Abstract: Predators influence prey populations not only through predation itself, but also indirectly through prompting changes in prey behaviour. The behavioural adjustments of prey to predation risk may carry nutritional costs, but this has seldom been studied in the wild in large mammals. Here, we studied the effects of an ambush predator, the African lion (Panthera leo), on the diet quality of plains zebras (Equus quagga) in Hwange National Park, Zimbabwe. We combined information on movements of both prey and predat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 35 publications
3
58
0
Order By: Relevance
“…, Barnier et al. , LaManna and Martin ). Conceptually, our understanding is limited because it is logical to hypothesize that the strength of antipredator responses should be positively related to the strength of direct predation (Relyea , Thaker et al.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…, Barnier et al. , LaManna and Martin ). Conceptually, our understanding is limited because it is logical to hypothesize that the strength of antipredator responses should be positively related to the strength of direct predation (Relyea , Thaker et al.…”
Section: Introductionmentioning
confidence: 97%
“…), diet (Christianson and Creel , Barnier et al. ), and physiology (Zanette , Clinchy et al. , Creel et al.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous tracking of caribou, moose, and wolves in anthropogenically disturbed habitats has revealed that the network connectivity of resource patches affects both the spatial dynamics of large herbivores and the hunting strategies of their predators (84). Simultaneous tracking has also been used to assess the feeding costs of antipredator behavior (85). However, caution is needed when drawing conclusions from such studies, as mismatches between sampling protocols and biological phenomena of interest can complicate inference.…”
Section: Science Sciencemagorgmentioning
confidence: 99%
“…That prey animals are altering their habitat use or behaviour by trading the decrease in forage quality or quantity over the higher security from predation is well documented (e.g. Sih 1980;Creel et al 2005;Kauffman et al 2007;Barnier et al 2014). However, the mechanism behind this trade-off is not easily understood.…”
Section: Introductionmentioning
confidence: 99%